Computer system web for coffee production management control - Cunha, Angélica Carvalho; Florentino, Ligiane Aparecida; da Silva, Adriano Bortolotti; Gabriel Filho, Luís Roberto Almeida; Putti, Fernando Ferrari (Coffee Science - ISSN 1984-3909, 2017)
Coffee cultivation in Brazil is concentrated in the southern region of Minas Gerais, where most of the properties have characteristics of family agriculture and often without the use of technology. Thus, many producers do not have production management control systems. In this way, the use of softwares that manage the productions becomes of paramount importance. Due to the competitiveness, different professional areas seek a technological efficiency to supply the growing demand, aiming agility in the execution of the processes. It is therefore imperative that technologically disadvantaged rural producers have the tools to make the enterprise more competitive. In this way, the objective of the present work was to develop a web system for property management. The system was developed from interviews with 10 coffee producers from the Southern Region of Minas Gerais, in which the need for online systems to assist in the management of properties was verified. This was done using the web programming language Personal Home Page ( PHP) and MySQL database for system development. It should be noted that the system has the characteristic of responsiveness, adapting in different sizes and formats of devices and also easy to use. The development of the system was of great relevance, since it contributes to a good management of the control of coffee production.